Targeted Cancer Therapy: The Role of Liposomes in Oncology. A Literature Review - Rudnicka, Katarzyna; Lemieszek, Paulina; Krukar, Katarzyna; Pustelniak, Martyna; Miga-Orczykowska, Nadia; Sajkiewicz, Ilona; Wójtowicz, Justyna; Jasiuk, Ilona; Łukaszewska, Ewa; Kister, Klaudia (Journal of Education, Health and Sport, 2024)
Liposomal formulations represent a significant advancement in the field of oncology, providing innovative solutions for the delivery of chemotherapeutic agents. These nanoscale carriers, made of phospholipid bilayers, enhance drug stability and allow for targeted delivery to tumor tissues, thereby improving the therapeutic index of anticancer medications. By altering the pharmacokinetics and biodistribution of these drugs, liposomes help reduce systemic side effects while increasing the concentration of therapeutic agents at the tumor site. Recent developments in liposomal technology have led to the creation of targeted liposomes, which can bind specifically to cancer cells, enhancing treatment accuracy. This review examines the various applications of liposomes in cancer treatment, discusses important clinical trials, identifies challenges in formulation and delivery, and considers future directions for integrating liposomal therapies into routine oncology practice. As ongoing research progresses, liposomes are poised to play a crucial role in advancing cancer treatment strategies and improving patient outcomes. Additionally, we discuss the challenges associated with their clinical translation and future perspectives in optimizing liposome formulations for personalized cancer therapies.